Exploring the Role of Artificial Intelligence (AI) in Designing and Optimizing Personalization Strategies to Enhance Customer Experience in the Tourism Industry - Nugroho, Ischak Suryo; Priyanto, Dwi; Purnama, Yulian (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to explore the role of Artificial Intelligence (AI) in designing and optimizing personalization strategies to enhance customer experience in the tourism industry. In a sector highly dependent on customer satisfaction and loyalty, AI technology offers innovative solutions that can deliver more relevant and tailored experiences. Through a qualitative literature review and descriptive analysis, this research examines the application of AI on digital platforms such as chatbots, data-driven recommendations, and customer behavior analysis in crafting personalized experiences. Case studies from leading companies such as Booking.com, Expedia, and Airbnb demonstrate how AI can improve operational efficiency and provide relevant recommendations to boost customer satisfaction. The study also addresses challenges in implementing AI, such as balancing automation with human interaction and issues related to personal data protection. This research provides insights into the importance of AI adoption in personalization strategies within the tourism industry and its implications for businesses and customers.